Study the Reality of Marketing Cut Flowers in Lattakia Governorate - سليمان, حيان; فاروسي, عمر; غانم , ريتا محمد (Latakia University Journal -Biological Sciences Series, 2021)
The environmental and climatic conditions in Lattakia have proven the ability to produce flowers that can be exported, and the locally produced flowers have proven their importance in supporting the national economy. Based on data collected from the research sample, based on the determination of the cost of materials and wages, the prevailing market prices for the years 2020 and 2021, and this research has been sought to achieve the following objectives: Studying the reality of the production and marketing of commercial cut flowers in Lattakia Governorate. Studying the marketing channels for cut flowers and knowing the obstacles encounter this. As a conclusion of study, the following results were reached: The problems faced by farmers were the prices of production requirements, seasonality of production, high transportation costs, rapid deterioration of flowers, and the lack of refrigerated storage places. The percentage of farmers who depend on wholesale stores to market their products is (79.3) %. The arithmetic average of the marketing costs amounted to (7268087.05) SP.